Answer:
y = - 2x + (1/2 38) + 2 = y = -2x + 19x + 2 at any second and y = -2x^2 / 2 + 19/2 + 2/2 = <u>- x^2 + 19/2 + 2 </u>= - x (4) + 19/2(4) + 1 = -4+ 38 + 1 = 35 seconds
Step-by-step explanation: We see that 38-2ft = 36ft and y intercept = 2 and then -2x allows us to represent the starting point 2 as -2 (1) to allow a descend to our back to 0 for y one we find y intercept we know - x^2 is our simplified equation and an input into this to find the static and slowed descend back to 0 if you keep inputting at 5 and 6 you see the equation speed up Anyway at (4) substitute = 4 seconds we divide our simplified equation a = -x2 into a b c and divide each by 2 before working out the<u> </u><u>decline</u> of the equation<u> (as equation still represents all ascending and descending) </u>for the 4th second as the height was <u>already said to be at its max at 38 feet see equation in answer to find 4 as substitute for x </u>
So basically to estimate your answer, you must
It’s non linear and it’s decreasing
Yes it is true! it is true because two different numbers go to the same number, if it was false it would have to be the one number to two different numbers.
Hope that made sense!
Answer:
When you calculate the average rate of change of a function, you are finding the slope of the secant line between the two points. f(x) = x2 and f(x + h) = (x + h)2 Therefore, the slope of the secant line between any two points on this function is 2x + h.